The role of regulatory B cell/T follicular helper cell balance in thymoma and thymoma-associated myasthenia gravis - Peng Zhang; Yuxin Liu; ZiYou Tao; Xinyu Zhang; Yuanguo Wang; Hui Zhang; Jian Li; Zhaoyu Yang; Kai Xiong; Shuning Duan; Zeyang Zhang; Yan Wang; et al. (Scientific Reports)
Abstract Thymoma is often associated with myasthenia gravis (MG). Abnormal lymphocyte differentiation often occurs in the thymoma tumor microenvironment (TME), leading to thymoma-associated autoimmune diseases. Thymoma is closely related to MG, although the underlying mechanisms remain unclear. Patients diagnosed with thymoma were selected and divided into three groups on the basis of MG diagnosis and severity: thymoma alone (T), thymoma-associated MG with mild and moderate clinical symptoms (T + MGL), and severe thymoma-associated MG (T + MGH). Tumor tissue and peripheral blood samples were collected from each group of patients. In the thymoma TME, CD19+ B cells, CD19+CD5+CD1d+ regulatory B cells (Bregs), CD4+ T cells, and CD4+CXCR5+ T follicular helper cells (Tfhs) were localized via multilabel immunofluorescence staining to clarify the relationship between local immune infiltration in the TME and MG severity. Bregs, Tfhs, and other immune cells in the peripheral blood were assessed by flow cytometry. B-cell-enriched regions were detected around blood vessels in the thymoma TME. Breg infiltration in the TME decreased with MG aggravation, whereas the opposite trend was observed for Tfh cells. The Breg/Tfh ratios in the peripheral blood and TME were broadly consistent, and the levels of both types of cells were significantly lower in patients with aggravated MG. Our findings revealed a balance among the Breg/Tfh ratio, immune hyperactivity, and immune tolerance in thymoma-associated MG in both the peripheral blood and the TME. These observations provide new perspectives regarding disease pathogenesis and immunotherapy.